Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
25 – 2x = 16 – 3x
-2x + 3x = 16 - 25
x = -9
Vậy x = -9
x - (47 - 22 ) = 5 + (10-4x)
x - 47 + 22 = 5 + 10 - 4x
x + 4x = 5 + 10 - 22 + 47
5x = 40
x = 40 : 5
x = 8
Vậy x = 8.
~ HOK TỐT ~
\(\text{25 – 2x = 16 – 3x}\)
\(2x+3x=16-25\)
\(5x=-9\)
\(\Rightarrow x=\frac{-9}{5}\)
\(\text{d) x – (47 – 22) = 5+ (10 – 4x)}\)
\(x-47+22=5+10-4x\)
\(x+4x=5+10-22+47\)
\(5x=40\)
\(\Rightarrow x=8\)
học tốt
2: 12-10x=25-30x
=>20x=13
=>x=13/20
3: \(3\left(2x+3\right)-2\left(4x-5\right)=10x+21\)
=>6x+9-8x+10=10x+21
=>10x+21=-2x+19
=>12x=-2
=>x=-1/6
4: \(\Leftrightarrow25x-15-6x+12=11-5x\)
=>19x-3=11-5x
=>24x=14
=>x=7/12
5: \(\Leftrightarrow8-12x-5+10x=4-6x\)
=>4-6x=-2x+3
=>-4x=-1
=>x=1/4
6: \(\Leftrightarrow32x-24-6+9x=13-40x\)
=>41x-30=13-40x
=>81x=43
=>x=43/81
7: \(\Leftrightarrow10x-5+20x=5x-11\)
=>30x-5=5x-11
=>25x=-6
=>x=-6/25
a, 70 - 5 ( x - 3 ) = 45
⇔ 5 . x - 3 = 70 - 45
⇔ 5 x - 3 = 35
⇔ x - 3 = 35 : 5 ⇔ x - 3 = 7
⇔ x = 10
b, 10 + 2 x = 4 5 : 4 3
⇔ 10 + 2 x = 4 2 ⇔ 10 + 2 x = 16
⇔ 2 x = 4 ⇔ x = 2
c, 60 - 3 x - 2 = 51
⇔ 3 x - 2 = 60 - 51
⇔ 3 x - 2 = 9
⇔ x - 2 = 3 ⇔ x = 5
d, 4 x - 20 = 2 5 : 2 3
⇔ 4 x - 20 = 2 2 ⇔ 4 x - 20 = 4
⇔ 4 x = 24 ⇔ x = 6
Mình làm 5 câu thôi nhé !:
1) \(7^x\cdot49=7^{90}\)
\(\Rightarrow7^x\cdot7^2=7^{90}\)
\(\Rightarrow7^{x+2}=7^{90}\)
\(\Rightarrow x=90-2\)
\(\Rightarrow x=88\)
2) \(2^x\cdot4=128\)
\(\Rightarrow2^x\cdot2^2=2^7\)
\(\Rightarrow2^{x+2}=2^7\)
\(\Rightarrow x=7-2\)
\(\Rightarrow x=5\)
3) \(3^x-1=2^4\cdot5\)
\(\Rightarrow3^x=80+1\)
\(\Rightarrow3^x=81\)
\(\Rightarrow3^x=3^4\)
\(\Rightarrow x=4\)
4) \(3^x+15=42\)
\(\Rightarrow3^x=42-15\)
\(\Rightarrow3^x=27\)
\(\Rightarrow3^x=3^3\)
\(\Rightarrow x=3\)
5) \(4\cdot2^x-3=125\)
\(\Rightarrow2^2\cdot2^x=128\)
\(\Rightarrow2^{x+2}=2^7\)
\(\Rightarrow x=7-2\)
\(\Rightarrow x=5\)
6)
\(5^x=5^{15}:5^3\\ \Leftrightarrow5^x=5^{15-3}\\ \Leftrightarrow5^x=5^{12}\\ \Leftrightarrow x=12\)
7)
\(4^x=4^{15}:16\\ \Leftrightarrow4^x=4^{15}:4^2\\ \Leftrightarrow4^x=4^{15-2}\\ 4^x=4^{13}\\ \Leftrightarrow x=13\)
8)
\(7^x=7^{20}:7^{10}\\ \Leftrightarrow7^x=7^{20-10}\\ \Leftrightarrow7^x=7^{10}\\ \Leftrightarrow x=10\)
9)
\(11^x=11^{11}:11\\ \Leftrightarrow11^x=11^{11-1}\\ \Leftrightarrow11^x=11^{10}\\ \Leftrightarrow x=10\)
10)
\(3^{15}.3^x=3^{30}\\ \Leftrightarrow3^x=3^{30}:3^{15}\\ 3^x=3^{30-15}\\ \Leftrightarrow3^x=3^{15}\\ \Leftrightarrow x=15\)
a) x- 18 = - 25
x =( -25 ) + 18
x = -7
b) 42 - x = 53 - 60
16 - x = 65
x = 16 - 65
x = -49
\(10-3x=25-4x\)
\(-3x+4x=25-10\)
\(x=15\)
k mk nha